Production of Ionic Imprinted Polymer from Nannochloropsis sp Biomass and its Adsorption Characteristics Toward Cu(II) Ion in Solutions - Buhani; Suharso; Sumadi (Asian Journal of Chemistry, 2011)
Material of Cu(II) ionic imprinted polymer from (Cu(II)-IIP) Nannochloropsis sp was synthesized via an immobilization of Nannochloropsis sp biomass with silica matrix from tetraethyl-orthosilicate (TEOS) precursor with a sol gel process followed with an ionic imprinting process using Cu(II) ion as a template. Characterizations of material were carried out using IR, XRD and surface area analyzer. Adsorptions of Cu(II) ions on non imprinted polymer (NIP) and Cu(II)-IIP are optimum at pH 5. Adsorption equilibrium follows Langmuir isotherm adsorption with the adsorption capacity of Cu(II) ion on NIP and Cu(II)-IIP of 54.24 and 94.71 mg g-1, respectively. The adsorption energies of Cu(II) ion on NIP and Cu(II)-IIP are 23.67 and 27.26 kJ mol-1. The adsorption competition data in an ionic pair solutions, Cu(II)/Cd(II); Cu(II)/Ni(II); Cu(II)/Zn(II); Cu(II)/Ag(I), show that Cu(II)-IIP is more selective than NIP with relative selectivity coefficient (at) of 40.16, 37.65, 31.74, 15.20 for concentration ratio of metal ions 1:1 and 38.48, 37.56, 29.25, 12.61, for concentration ratio of metal ions 1:2, respectively. The material of Cu(II)-IIP is stable chemically and it can be reused on the adsorption of Cu2+ in solutions with the recovery percentage higher than 97 %.